Comprehensive practical evaluation of wired and wireless internet base smart grid communication. Issue 5 (24th March 2021) - Zeinali, Mehdi; Thompson, John
Abstract: Internet‐based communications is a key solution for enabling low‐cost and scalable communication infrastructure for different applications of the smart grid. However, the performance of this network needs to be evaluated practically in the context of smart grid applications based on key metrics such as latency and reliability. This article is a comprehensive evaluation of the United Kingdom Internet network characteristics which will allow the smart grid systems designer to consider the essential parameters for communication applications. This article will focus not only on three smart grid applications, but also the outcome of this research which is relevant to a wider range of Internet of Things (IoT) applications. Different combinations of off‐the‐shelf wired and wireless last‐mile communication technologies are evaluated using real‐world transport protocols such as the Transport Control Protocol (TCP)and the User Datagram Protocol (UDP). The performance of TCP/UDP has been tested in a realistic client‐server communication test‐bed. The results from extensive evaluations show that typical latency values are between 200 and 600 ms for data packets and 50 bytes and  kbytes for short control packets. Moreover by applying data compression techniques, the results can be improved about 5%–20% for different last mile communications.